2013
DOI: 10.1159/000345403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Problems and Relationship between Sleep Problems and School Refusal Behavior in School-Aged Children in Children's and Parents' Ratings

Abstract: Objective: This cross-section study investigated the prevalence of sleep disorders and the relationship between sleep problems (insomnias, parasomnias, and daytime sleepiness) and school refusal behavior in school-age children (fourth grade elementary school in Cologne, Germany). Method: A sample of 1,490 children (age range: 8-11 years) and their parents each completed a sleep questionnaire and the School Refusal Assessment Scale. Results: The results indicate that sleep problems in childhood are frequent. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 33 publications
(54 reference statements)
2
25
0
5
Order By: Relevance
“…Results of the present study showed that individuals with specific learning disorder (SLD) (65.5%) presented higher percentages of sleep disturbance compared with those of individuals with typical development assessed in this and other studies (up to 40%) (23,24) . Considering that sleep plays an essential role in the processes of attention, memory formation, and brain plasticity and maturation, the data of this study emphasize the importance of investigating the quality of sleep and its disorders in conditions involving deficits in neural processes (9,12) , such as SLD (12) .…”
Section: Discussionsupporting
confidence: 41%
“…Results of the present study showed that individuals with specific learning disorder (SLD) (65.5%) presented higher percentages of sleep disturbance compared with those of individuals with typical development assessed in this and other studies (up to 40%) (23,24) . Considering that sleep plays an essential role in the processes of attention, memory formation, and brain plasticity and maturation, the data of this study emphasize the importance of investigating the quality of sleep and its disorders in conditions involving deficits in neural processes (9,12) , such as SLD (12) .…”
Section: Discussionsupporting
confidence: 41%
“…Despite high prevalence rates and the adverse consequences linked to this problem, there are limited available instruments to specifically assess this construct, especially for Spanish students (Inglés et al, 2015; García-Fernández et al, 2016). At the international level, the School Refusal Assessment Scale for Children-Revised (SRAS-R-C; Kearney, 2002a) is the most commonly used assessment scale, and it is mainly applied in American (Kearney, 2016), French (Brandibas et al, 2001, 2004), German (Hochadel et al, 2014), Korean (Kim, 2010), English (Richards and Hadwin, 2011), and Turkish (Seçer, 2014) populations. Other instruments to evaluate school refusal have been proposed to assess this construct, such as the scale Feelings of School Avoidance (Watanabe and Koishi, 2000), School Avoidance Scale (Fujigaki, 1996), and School Refusal Personality Scale (Honjo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Additional research is thus needed regarding the factorial structure of the SRAS-R-C, especially in Spanish students. There are studies that have used this scale with children aged between 5 and 9 years (Kearney et al, 2005) and 8–11 years (Hochadel et al, 2014). However, there are not previous validations of the SRAS-R-C with pre-adolescents, whereas there are different validations of this scale only with adolescents (Lyon, 2010; Haight et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Youth with school refusal behavior do tend to have social functioning problems and withdraw from friends and other peers at school (Havik et al, 2015;Gonzálvez et al, 2019). Others indeed show difficulties with sleep (including going to bed very late), energy, and physical activity (Ek and Eriksson, 2013;Hochadel et al, 2014;Mannino et al, 2019). However, each set of behaviors -social and sleep problems and school attendance problems -may precede the other in different cases (Kearney, 2019).…”
Section: Discussionmentioning
confidence: 99%